Đo lường tăng trưởng kinh tế bao trùm ở Việt Nam: Cách tiếp cận mới với thước đo mới - Pham Thi Bich, Ngoc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Inclusive growth emphasizes equity in the distribution of opportunities and benefits arising from economic development, particularly for vulnerable groups. However, there is a lack of measures to evaluate inclusive growth. This paper introduces and applies the Upward Mobility Measure proposed by Ray and Genicot (2023) to measure how much the poor have benefited from economic growth in Vietnam between 2002 and 2020. Using data from the Vietnam Household Living Standards Survey (VHLSS), the results reveal that the poor have benefited from economic growth, thereby confirming the inclusive nature of growth in Vietnam. This study also demonstrates the potential application of this measure for cross-country or regional comparisons of growth inclusiveness, offering a valuable tool to inform the design of equitable and sustainable development policies.